2011
DOI: 10.3341/kjo.2011.25.5.305
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Lens-Sparing Vitrectomy for Stages 4B and 5 Retinopathy of Prematurity

Abstract: PurposeTo assess long-term anatomic and visual outcomes and associated complications of lens-sparing vitrectomy (LSV) for treatment of tractional retinal detachments (TRDs) associated with stages 4B and 5 retinopathy of prematurity (ROP).MethodsWe performed a retrospective review of medical records and data analyses of consecutive patients who presented with stages 4B and 5 ROP and underwent LSV from 1999 to 2007. Retinal reattachment status, visual acuity and postoperative complications were evaluated.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Once retinal detachment occurs, the visual outcomes are generally poor (Quinn et al, 1991, Seaber et al, 1995, Trese and Droste, 1998, Shah et al, 2009b, Singh et al, 2012, with the best anatomical success rates at around 50% for stage 5 disease (Gadkari et al, 2015), but frequently as low as 15-25% (Shah et al, 2009b, Yu et al, 2006, Choi et al, 2011. Poor results and severe complications have been reported, even with lens-sparing vitrectomy (Yu et al, 2006).…”
Section: Vitrectomy -Structural and Visual Outcomesmentioning
confidence: 99%
“…Once retinal detachment occurs, the visual outcomes are generally poor (Quinn et al, 1991, Seaber et al, 1995, Trese and Droste, 1998, Shah et al, 2009b, Singh et al, 2012, with the best anatomical success rates at around 50% for stage 5 disease (Gadkari et al, 2015), but frequently as low as 15-25% (Shah et al, 2009b, Yu et al, 2006, Choi et al, 2011. Poor results and severe complications have been reported, even with lens-sparing vitrectomy (Yu et al, 2006).…”
Section: Vitrectomy -Structural and Visual Outcomesmentioning
confidence: 99%
“…Cataract formation is a known risk factor after vitrectomy in cases with ROP. Choi et al 5 found that cataract developed in 19% of patients after LSV over a mean follow-up period of 5.6 years. In our series, the mean time to diagnosis of cataract after vitreous surgery was 7.76 months (range 2–32 months).…”
Section: Discussionmentioning
confidence: 99%
“…Cataracts in these infants may occur spontaneously or may be related to the interventions undertaken to treat the underlying retinal pathology, such as laser3 or vitreous surgery 4 5…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in foveal architecture that reduce central acuity and thereby result in eccentric fixation have been reported in children who developed severe ROP, especially those who had a vitrectomy or retinal re-attachment surgery 12 .…”
Section: Discussionmentioning
confidence: 99%